Self-perceived competency and self-perceived employability in higher education: the mediating role of career adaptability - Monteiro, Sílvia Correia (2020)
In a time where employability issues are at the top of political agendas and employment prospects represent the most important predictor of satisfaction with higher education, the question about how higher education institutions can better prepare their graduates for the labour market becomes increasingly important. Taking the career construction theory as its main theoretical framework, this study intends to explore the role of career adaptability as a mediating variable between competencies developed during higher education studies and perceived employability. The participants were 373 students attending the last year of master’s degree programmes, who completed the Career Adapt-Abilities Scale, the Self-Perceived Employability Scale, and a survey exploring students’ perceptions about their competencies at the end of their university programme. The results indicated that career adaptability has a mediating role between self-perceived competency and selfperceived employability. Although academic competencies represent a prerequisite for employability, the ﬁndings suggest that graduating students should also be equipped with career management resources to handle their own attributes and to transition smoothly into the current labour market. These ﬁndings are particularly important because they reveal how higher education institutions can foster the employability of graduates by integrating training opportunities in career management during graduation programmes.